ROTENONE ISOLATION AND IDENTIFICATION OF STEROLS IN THE HOME OF YAWAR PANGA (Aristolochia cf. Cauliflora Ule. or Aristolochia Didyma) - Rojas Rodriguez, Luis (2022)
Plants with therapeutic properties are commonly used in traditional medicine, such is the case of Yawar Panga, Aristolochia cf. Cauliflora Ule. No studies on the chemical composition of Yawar Panga leaves, or any other part of the plant, have been published in the literature. From the petroleum ether and dichloromethane extracts of the leaves of Yawar panga, collected in the Botanical Garden of the Takiwasi Center (Tarapoto, San Martín region, PeruvianAmazon), three sterols, γ-sitosterol, stigmasterol and campesterol, were identified, which were analyzed by gas chromatography and identified through their spectra of masses (CGEM). Likewise, rotenone (with 93.4% purity) was isolated from the ethanolic extract, which was identified by CG-EM, 1H and 13C nuclear magnetic resonance (RMN 1H and RMN 13C) and by Fourier transform infrared spectroscopy (FTIR).